IMPLEMENTATION OF GOTO TRADEMARK PROTECTION BASED ON THE PRINCIPLE OF “SUBSTANTIAL SIMILARITY” - Richie Fernando; Gunawan Djajaputra (Universitas Bengkulu, 2025)
Trademark protection is a crucial aspect of intellectual property law, aimed at safeguarding trademark owners and preventing consumer confusion. This study analyzes the implementation of the